Analysis of Cyclical Unemployment Impacted by COVID-19 in Indonesia: Inter-Island Study Based on 2020 Sakernas Data - Harumi, Wise; Bachtiar, Nasri; Kamarni, Neng (Akuntansi & Ekonomika, 2026)
This study is motivated by the rise of cyclical unemployment during the Covid-19 recession, particularly in the form of temporary layoffs. Temporary unemployment differs from permanent unemployment because workers still have the possibility of being recalled to their jobs. This study aims to analyze the risk of individuals across Indonesian islands becoming temporarily unemployed due to Covid-19 and to examine the probability of receiving a job recall guarantee. A quantitative approach was employed using microdata from the August 2020 National Labor Force Survey (Sakernas), analyzed through logistic regression. The findings from 13,805 samples show that the highest risk of temporary unemployment occurred in Bali and Nusa Tenggara, especially in urban areas, where the risk was 4.348 times higher than in other islands. Young workers aged 15–24 also faced a 1.647 times higher risk. These results reflect the region’s dependence on tourism.